2014
DOI: 10.1186/1756-0500-7-758
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with nonadherence to diet and physical activity among nepalese type 2 diabetes patients; a cross sectional study

Abstract: BackgroundNonadherence to diet and physical activity is a major problem in the management of diabetes mellitus and its complications. This study was undertaken to measure the factors associated with nonadherence to diet and physical activity advice among Nepalese type 2 diabetic patients.MethodsAn analytical cross-sectional study was conducted among type 2 diabetic patients (age, M ± SD, 54.4 ± 11.5 yrs) and interviewed using three days recall method for dietary history and Compendium of Physical Activity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

24
108
14
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(179 citation statements)
references
References 23 publications
24
108
14
2
Order By: Relevance
“…Besides, failures in the provision of information were associated to low adherence to drug treatment, lack of regular physical exercise, and consumption of foods with high sugar content. These findings are coherent with previous studies which mentioned that not having received or understood the information about portions and the frequency of meals may be associated with low adherence to diet in diabetic patients (Ranasinghe et al, 2015;Cheng et al, 2016;Parajuli, Saleh, Thapa & Ali, 2014). Thence, it is important that the information provided to the diabetic patient has clear recommendations for self-care, expressed in a kind of language that the patient may fully understand.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, failures in the provision of information were associated to low adherence to drug treatment, lack of regular physical exercise, and consumption of foods with high sugar content. These findings are coherent with previous studies which mentioned that not having received or understood the information about portions and the frequency of meals may be associated with low adherence to diet in diabetic patients (Ranasinghe et al, 2015;Cheng et al, 2016;Parajuli, Saleh, Thapa & Ali, 2014). Thence, it is important that the information provided to the diabetic patient has clear recommendations for self-care, expressed in a kind of language that the patient may fully understand.…”
Section: Discussionsupporting
confidence: 90%
“…Their preferred health message disseminator was, in order of preference, a doctor, nurse, other health professional and trained community members (community health care workers). This may be as a result of the fact that these health professionals are regarded as having expertise in health matters confirming the findings of Parker, Steyn, Levitt, and Lombard (2012), Parajuli, Saleh, Thapa, and Ali (2014) and Levesque et al (2012). These authors found that adherence to interventions worked better when the doctor is the source of the information as this allowed patients to build a relationship with the person disseminating the health messages and facilitated discussing their problems.…”
Section: Discussionsupporting
confidence: 66%
“…Studies have reported compliance ranging from 12% to 63% for dietary advice amongst diabetic patients. 16,17,[24][25][26] Majority of the respondents in our study had made minor omissions or additions in their diet. In our study compliance was defined as any modification in diet as per the advice provided during the camp.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have reported a compliance ranging for 48% to 75% for exercise among diabetic patients. 17,[24][25][26] The commonest physical activity taken up by the respondents was walking. This is an option which can be easily practiced as it does not need special equipment or resources.…”
Section: Discussionmentioning
confidence: 99%